Studies on the biology of the Cape chestnut psylla paurocephala Calodendri Moran (in press) and the South African citrus psylla Trioza Erytreae (Del Guercio) (Homoptera : Psyllidae) - Moran, V C (V. Cliff) (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1968)
Citrus is grown as a commercial crop in several areas surrounding Grahamstown in the Eastern Cape Province of South Africa. Twelve miles South-west of Grahamstown is an orchard of about 6000 trees on the farm "Mosslands". This orchard attracted attention as the insect pests of citrus have been kept at a sub-economic level by natural biological control since 1949. This orchard is completely surrounded by indigenous bush and originally the object of this study was to see, in how far, the insect fauna of the indigenous bush was infuencing the biological control which had been achieved in the orchard. As citrus is a member of the family Rutaceae, four indigenous plants in this family, which occured in the indigenous bush, were chosen for a closer study of their associated insect fauna. This study continued for a year during which time a bewildering number of insects and their parasites were collected and it was realized that only an investigation of a very specific aspect of the problem could possibly yield meaningful results. As a starting point, therefore, Trioza erytreae (Del Guercio) (Homoptera: Psyllidae), the South African citrus psyllid, was singled out. This psyllid was found on citrus at "Mosslands" and was also found on all but one of the indigenous rutaceous plants. It was chosen for study because of its polyphagous habit and because very little is known of the biology of this economically important species in South Africa. Also very little work has been done on the Psyllidae generally. Intro., p. 1.
Keywords: Citrus -- Diseases and pests -- South Africa; Psylla